The contribution of G.M. Borlikov to the solution of ecological problems of Kalmykia and the Caspian region - G. E. Nastinova (Юг России: экология, развитие)
An essay on the contribution of German Mandzhievich Borlikov to the study of problems of desertification and the development of proposals to ensure the rational use of natural resources in Kalmykia and in the Caspian region as a whole, thanks to his researches, many of which were carried out with colleagues from Kalmykia State University, leading research institutes and universities in Russia and other countries. A noteworthy result of scientific research in the field of protection and rational use of soils conducted by G.M. Borlikov, L.Kh. Sangadzhieva and V.A. Bananova was the thematic mapping of the soil resources of Kalmykia.